FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI KADER DALAM PELAKSANAAN POSYANDU DI WILAYAH KERJA PUSKESMAS DUHIADAA KECAMATAN DUHIADAA KABUPATEN POHUWATO TAHUN 2019 - Harismayanti Harismayanti; Ani Retni (-, 2021)
The purpose of this study was to determine the factors related to cadre participation in the implementation of posyandu at the Duhiadaa Health Center In Pohuwato District. This type of research is an observational method with a cross sectional study. With a sample of 80 people and the result obtained are the level of knowledge of cadres related to the participation of the cadres in the implementation of posyandu (x2 count > X2 table) with avalue of 11.098> 3.841 where is the value of P (0.001 <60.05), attitude related to cadre partipation in the implementation of posyandu (19.850> 3.841) where the p value (0.00<đ0.05), the training was related to the participation of cadres in the implementation of posyandu (19.901>3.841) where the P value (0.00<60.05).